How Participatory Are We Really? The Pitfalls and Potentials of Participatory Research Practices - Eriksson, Birgit; Stage, Carsten (Conjunctions. Transdisciplinary Journal of Cultural Participation, 2024)
The development of participatory research practices has been linked to high hopes of creating more relevant, socially robust, and democratic forms of academic knowledge. Researchers have, however, also pointed to a discrepancy between the ideals and realities of participation, in research and elsewhere. This paper uses these critiques of participation to unfold the dilemmas of two participatory projects: RECcORD: Rethinking European Cultural Centers in a European Dimension (2015-17) and Participate: Citizen Participation in Danish Cultural Centers (2019-23). Both projects approached participation as a method that involved co-researching participants from cultural centers, and as a practice to be explored while unfolding in the centers. This paper critically discusses the methodologies of the projects by developing an evaluative framework that highlights both the participatory potentials and pitfalls of the two processes. This transferable framework is based on the concepts of ‘unpredictability’, ‘friction’, ‘autonomy’, ‘inequality’, ‘failure’, and ‘scale’.